Autoimmune T cell repertoire in optic neuritis and multiple sclerosis: T cells recognising multiple myelin proteins are accumulated in cerebrospinal fluid. Issue 5 (May 1994) - Söderström, M; Link, H; Sun, J B; Fredrikson, S; Wang, Z Y; Huang, W X
Abstract : Monosymptomatic unilateral optic neuritis is a common first manifestation of multiple sclerosis. Abnormal T cell responses to myelin components including myelin basic protein (MBP), proteolipid protein (PLP), and myelin-associated glycoprotein (MAG) have been implicated in the pathogenesis of multiple sclerosis. Antigen-reactive T helper type 1 (Th1)-like cells that responded by interferon gamma (IFN-gamma) secretion on antigen stimulation in vitro were counted. Untreated patients with optic neuritis and multiple sclerosis had similarly raised levels of T cells recognising MBP, PLP, and MAG in peripheral blood. Such T cells were strongly enriched in CSF. None of these myelin antigens functioned as immunodominant T cell antigen characteristic for optic neuritis or multiple sclerosis. The autoimmune T cell repertoire was not more restricted in optic neuritis (as an example of early multiple sclerosis). The autoreactive T cell repertoires differed in blood compared with CSF in individual patients with optic neuritis and multiple sclerosis. No relations were found between specificity or quantity of autoreactive T cells in blood or CSF, and clinical variables of optic neuritis or multiple sclerosis, or occurrence of oligoclonal IgG bands in CSF. The role of raised MBP, PLP, and MAG reactive Th1-like cells found in optic neuritis and multiple sclerosis remains unexplained.